2012
DOI: 10.1016/j.artmed.2011.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian tracking of intracranial pressure signal morphology

Abstract: Background The waveform morphology of intracranial pressure (ICP) pulses holds essential informations about intracranial and cerebrovascular pathophysiological variations. Most of current ICP pulse analysis frameworks process each pulse independently and therefore do not exploit the temporal dependency existing between successive pulses. We propose a probabilistic framework that exploits this temporal dependency to track ICP waveform morphology in terms of its three peaks. Material ICP and electrocardiogram … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 26 publications
0
15
0
Order By: Relevance
“…2), which still holds pulsatile information, is the “ground truth” that will further be used in our experiments. As it has been shown in previous works [9,12], the average shape of the ICP waveform is related to the ICP elevation. Pulses corresponding to normal ICP tend to exhibits three peaks (in blue), while higher ICP ones generally tend to become unimodal (in red).…”
Section: Methodsmentioning
confidence: 52%
See 2 more Smart Citations
“…2), which still holds pulsatile information, is the “ground truth” that will further be used in our experiments. As it has been shown in previous works [9,12], the average shape of the ICP waveform is related to the ICP elevation. Pulses corresponding to normal ICP tend to exhibits three peaks (in blue), while higher ICP ones generally tend to become unimodal (in red).…”
Section: Methodsmentioning
confidence: 52%
“…In contrast to previous works [22,9], our method captures the continuously varying characteristics of ICP waveforms. This was accomplished by characterizing the morphology of ICP waveforms via clustering, warping the subspace using continuous valued statistics (DC value and expert annotations), and tracking the progression of waveforms within the proposed I/CST framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted suggesting use of machine learning methods and probabilistic frameworks to understand the characteristics in waveform morphology linked to elevated intracranial pressure [8], [9], [10]. A study by colleagues at UCLA demonstrated key relationships between ICP sub-peaks and hypertension [11].…”
Section: Introductionmentioning
confidence: 99%
“…In this section, we present a probabilistic framework [24] to track ICP peaks in real time. The tracking is posed as inference in a graphical model that associates a continuous random variable to the position of each of the three peaks, in terms of their latency within the pulse and pressure level.…”
Section: Bayesian Tracking Of Icp Morphologymentioning
confidence: 99%